2008
DOI: 10.1038/jhh.2008.41
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of new-onset diabetes mellitus in hypertensive patients: the VALUE trial

Abstract: Diabetes mellitus often develops in patients with hypertension. We investigated predictors of diabetes mellitus development in hypertensives at risk of developing the disease in the VALUE trial population. Among the 9995 non-diabetic hypertensive patients at baseline, 1298 patients developed diabetes mellitus during the average follow-up of 4.2 years. New-onset diabetes mellitus was defined from adverse event reports, information about new antidiabetic medication and/or a fasting glucose X7.0 mmol l À1 at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
(36 reference statements)
2
17
0
Order By: Relevance
“…Despite this, the association between elevated resting heart rate and type 2 diabetes remains unclear (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Some studies suggested an increased risk of type 2 diabetes with higher heart rate (6;7;10;12-17), whereas others found the association to be no longer significant after adjustment for potential confounding factors (8;9;11).…”
Section: Introductionmentioning
confidence: 98%
“…Despite this, the association between elevated resting heart rate and type 2 diabetes remains unclear (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Some studies suggested an increased risk of type 2 diabetes with higher heart rate (6;7;10;12-17), whereas others found the association to be no longer significant after adjustment for potential confounding factors (8;9;11).…”
Section: Introductionmentioning
confidence: 98%
“…Different antihypertensive treatments seems to have different impacts on diabetes incidence, and in particular, the RAAS modulating agents appear to have a protective role against diabetes development. [2][3][4] It is also possible that common genetic patterns could influence both HTN and diabetes incidence. The environmental causes of these diseases are actually well known.…”
mentioning
confidence: 99%
“…2 However, in the large Valsartan Antihypertensive Long-term Use Evaluation trial, in which 9995 patients were enrolled with 1298 cases of incident diabetes, HTN was not a significant predictor of diabetes. 3 The physiopathological link between HTN and diabetes in lean subjects primarily involves the renin-angiotensin-aldosterone system (RAAS). This hypothesis is supported by numerous preclinical tests and by the results of some large clinical trials.…”
mentioning
confidence: 99%
“…21 Pretreatment plasma glucose is by far the most important predictor of new-onset diabetes. 22,23 In various populations, there is a continuous relationship between plasma glucose or HbA lc and cardiovascular outcomes, even at levels below the threshold for diabetes. [24][25][26] Thus, the excess risk of cardiovascular events in new-onset diabetes may be associated with plasma glucose status long before the diagnoses or the introduction of therapy.…”
mentioning
confidence: 99%